Two-dimensional in vivo rectal dosimetry during high-dose-rate brachytherapy for cervical cancer: a phantom study. (3rd October 2018) - Jeang, Eun Hee; Goh, Youngmoon; Cho, Kwan Ho; Min, Soonki; Choi, Sang Hyoun; Jeong, Hojin; Jo, Kwanghyun; Lee, Nuri; Song, Sanghyeon; Lee, Se Byeong; Shin, Dongho; Kim, Yeon-Joo; et al.
Abstract: Background: The aim of the present study was to verify the dosimetric accuracy of two-dimensional (2D) in vivo rectal dosimetry using an endorectal balloon (ERB) with unfoldable EBT3 films for high-dose-rate (HDR) brachytherapy for cervical cancer. The clinical applicability of the technique was discussed. Material and methods: ERB inflation makes the EBT3 films unrolled, whereas its deflation makes them rolled. Patient-specific quality assurance (pQA) tests were performed in 20 patient plans using an Ir-192 remote afterloading system and a water-filled cervical phantom with the ERB. The dose distributions measured in ERBs were compared with those of the treatment plans. Results: The absolute dose profiles measured by the ERBs were in good agreement with those of treatment plans. The global gamma passing rates were 96–100% and 91–100% over 20 pQAs under the criteria of 3%/3 mm and 3%/2 mm, respectively, with a 30% low-dose threshold. Dose-volume histograms of the rectal wall were obtained from the measured dose distributions and showed small volume differences less than 2% on average from the patients' plans over the entire dose interval. The positioning error of the applicator set was detectable with high sensitivity of 12% dose area variation per mm. Additionally, the clinical applicability of the ERB was evaluated in volunteers, and none of them felt any pain when the ERB was inserted or removed. Conclusions: The 2D in vivo rectal dosimetry using the ERB with EBT3 films was effective and might be clinically applicable for HDR brachytherapy for cervical and prostate cancers to monitor treatment accuracy and consistency as well as to predict rectal toxicity.